PEMELIHARAAN EKOSISTEM PANTAI MELALUI EDUKASI KEBERSIHAN PESISIR DAN HUTAN MAGROVE DI PANTAI CEMARA – LEMBAR , NTB - Ariyani, Etika; Lutfia, Nayla (E-Amal: Jurnal Pengabdian Kepada Masyarakat, 2024)
This community service program aims to give education for coastal community at cemara beach, Lembar – West Lombok about the importance of coastal cleanliness to maintain coastal ecosystem, minimize dangerous impact of plastic waste and coastal clean-up movement. This program held to improve community participation to keep coastal area clean. The level of public awareness in Cemare beach coastal area still low, it is indicated by accumulation of plastic rubbish everywhere in that area. The method used in this community service was counselling and coastal clean-up movement by collected plastic waste around coastal area together. This program give positive impact to public awareness in order to preserving coastal ecosystem. This activity supported by local government and youth association, it held very interesting and useful to arouse public awareness and keep coastal area clean regularly. The positive result of this community service program can minimize rubbish accumulation spots along coastal area and maintain mangrove forest ecosystem. The expected outputs from this program were community can understand and apply awareness of beach cleanliness to increase economic growth from marine tourism in West Nusa Tenggara Province